Childfree and Inheritance Rights in Islamic Family Law: A Comparative Review - Bambang Sutrisno; Rika Handayani (Indonesian Journal of Islamic Law, 2020)
This research investigates the legal and social implications of childfree decisions on inheritance rights in Islamic family law through a comparative juridical approach. The phenomenon of childfree, namely the decision of a husband and wife not to have children, raises questions about how inheritance rights are regulated and implemented in accordance with Islamic law. This study analyzes various views from the main schools of Islam (Hanafi, Maliki, Syafi'i, and Hanbali) as well as fatwas from leading fatwa institutions such as Dar al-Ifta al-Misriyyah and the Indonesian Ulema Council. The research results show that the childfree decision influences the social structure of the family and brings significant changes in the distribution of inheritance rights. Analysis of actual cases reveals that the absence of children in a family can transfer part of the inheritance to other relatives such as siblings or parents. This research recommends the need for increased education and inclusive legal guidance to reduce social stigma and ensure fairness in inheritance distribution, so that Islamic family law can be more responsive to contemporary social dynamics.